The Influence Of Aquifer Mineralogy On Groundwater Hydrochemistry, Merapi Volcano Southern Slope Area, Sleman Regency, Yogyakarta Special Region - Ayu Narwastu Ciptahening; Sari Bahagiarti Kusumayudha; Noppadol Phien-wej (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2026)
People living in the southern slope of Merapi volcano generally consume groundwater for drinking needs. The source is Merapi aquifer that formed of various volcanic deposits, consisting of fractured-weathered breccia, weathered lava, and bouldery sand, with rock petrologically andesitic to basaltic. In one place, groundwater shows good quality, but in another place it can be different, making the people grumble about. Therefore things influencing the groundwater quality needs to be identified suitably, and this study required to be conducted. Objective of the study is to assess the influence of aquifer mineralogy and geochemistry, on groundwater quality. Method being applied was petrological, geochemistry, and hydrochemical assessments. The result shows that in the study area groundwater predominantly contains cations of Ca2+, Mg2+, and Na+, while anions predominantly consist of HCO3, SO42-, and Cl-. Hydrochemical facies are classified into Ca-Mg-HCO3, Ca–HCO3, some samples show mixing type, and Na-Cl facies. Mineral composition of the aquifer strongly influence in the groundwater cation contents, environmental process lead the anion contents, while the Na-Cl facies sample is interpreted caused by domestic waste contamination